The Effect of Peer Education on the Behavior of Snack Consumption in Gorontalo Regency - Deby Sinta Darise; Healthy Hidayanty; Suriah Suriah; Veni Hadju; Burhanuddin Bahar; Erniwati Ibrahim (Newinera Publisher, 2021)
Teenagers are very vulnerable to the influence of their environment. A socio-cultural environment that is not positive is a risk factor for adolescents in unhealthy behavior. Snack habits are part of behavior in the form of action. The habit of consuming snacks for students in Gorontalo reaches 78.4%. The research objective was to see the effect of peer education on knowledge, attitudes and actions of snack consumption among adolescents. This research was a quasi-experiment with a pre-test post-test control group design. The research was conducted on 19 adolescents at SMP Negeri 1 Limboto Barat and 19 adolescents at SMP Negeri 1 Boliyohuto. Duration of intervention twice a week for two weeks. Data analysis used paired t-test and independent t-test. The results showed that there were no differences in the characteristics of gender (p = 0.330), class (p = 0.744), age (p = 0.148) and pocket money (p = 0.461). There is an effect of peer education on knowledge (p = 0.001) and attitude (p = 0001). Based on the difference between the peer education group and the leaflet, there was a difference in the score selection for knowledge (p = 0.001) and attitude (p = 0.001), but there was no difference in the score selection for the measures (p = 0.805). The conclusion of this study is that the peer education method has an effect on increasing knowledge and attitudes regarding snack consumption. Peer education suggestions can be used as an approach by schools for students to reduce the number of snack consumption habits in adolescents.